(untitled) (Research, Society and Development, 2020)
The main objective of this work was to quantify the phenolic compounds, and to evaluate antioxidant and antimicrobial the activity of Croton cajucara BENTH stem bark extracts. An experimental planning (Box Hunter and Hunter) of two factors and two levels determine which variables influenced in the extraction process was used. To the quantification of phenolic compounds was used the methodology of Folin-Ciocalteau. To the antioxidant activity the IC50 method was applied. For the antimicrobial analysis, the microdilution method was employed to indicate the Minimum Inhibitory Concentration (MIC) against the bacterial strains, as well as fungal strain. In the quantification of phenolic compounds, there was a variation between 26.98 and 50.32 mgEAG /g. Regarding antioxidant activity, values from 9.01% to 14.03% were found. For antimicrobial activity, the extracts did not inhibit the growth of the tested bacteria and fungi. All the results were treated statistically and, in general, proved that the best extraction conditions were T = 60 °C and G = 0.10 mm.